Evaluation of the student-athlete education and training center (SAETC) development program Jambi Province - Ningsih, Mardiana; Sukendro, Sukendro; Indrayana, Boy (Universitas Tanjungpura, 2026)
Background. The Student-Athlete Education and Training Center (SAETC) is expected to be a place for young athletes to train and develop their talents and abilities, which will later become a benchmark and place for outstanding athletes. Objectives. This study aims to develop and test the validity of the Hybrid Sports Education Model Teaching Factory (The purpose of this research is to find out the results of the Jambi Province SAETC Development Program. Methods. This study uses a qualitative descriptive method with the CIPP Model. Information collection through observation, interviews, both structured and unstructured, documentation, visual materials, and efforts to design protocols to record/record information. Overall, the program has succeeded in producing more competitive athletes, with the hope of continuing to improve resources and training programs for the development of better athlete potential in the future. Results. This research shows that the coaching program at the Jambi Province Student Education Training Center is in a supportive context, despite facing external challenges such as lack of community support and suboptimal infrastructure. Input aspects include the quality of experienced trainers, adequate facilities, and adequate funding, although facilities and infrastructure still need improvement. The program implementation process is structured with a regular training schedule and periodic evaluations by trainers, although funding and logistical barriers affect its smoothness. Conclusion. As a result, athletes show significant improvements in achievement, winning medals at national and international championships, reflecting the effectiveness of the program in developing athlete potential, both technically and characterfully. In the future, the results of this research are expected to make a new and significant contribution to the development of strategies for fostering outstanding athletes at the regional and national levels.